The Determination of Safe Concentration of Non-Carcinogenic Toluene in Surabaya Printing - Ahmad Rido'i Yuda Prayogi; Abdul Rohim Tualeka; Ahsan Ahsan; Pudji Rahmawati; Syamsiar S Russeng; Indri H Susilowati (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Safe concentrations of non-carcinogenic toluene can cause adverse effects on health. Based on the results of a research, toxic effects on toluene exposure can cause cancerous (leuikimia) and non-cancerous (aplastic anemia). The Research objective to determine the safe concentration of non-carcinogenic toluene in Surabaya printing. Methods: The research design used was observational analytic, cross sectional research design with a quantitative approach. The research location was a printing press in Surabaya. The variables in this study were the concentration of toluene levels (ppm) and RQ in workers. Total population was 37 workers, while the study sample was taken using accidental sampling method with a total sample of 30 respondents. The formula for determining the concentration of toluene non carcinogen intake is (CxRxtExfExDt): (Wbx30x365). Results: The concentration value of toluene exposure was greater than the standard set by labor regulations No. 5 of 2018 about occupational health and safety of the work environment by 0.2 ppm. A total of 10% of workers falls under normal category, 73% above normal category and 27% below normal category. Conclusion: In this study, we found new findings, viz the concentration of toluene exposure in Surabaya printing area was above normal with a concentration of 0.2 ppm and this is considered not normal.Keywords: non carcinogenic toluene, safe concentration, surabaya printing, toluene